The last witch - Cooke, C. J., 1978- (Berkley, 2025)
"Helena Scheuberin should be doing what every other young wife is doing: keeping house, supporting her husband, and bearing his children, but as an outspoken, strong woman, she sometimes has difficulty fitting in. Then she draws the unwanted attention of a malign priest who is just starting his campaign to root out "witches" from among the women of her town, and when her husband's footman dies, she finds herself accused not only of murder but of witchcraft. Helena must find the courage to risk her life and the lives of others by standing up to a man determined to paint her as the most wicked of all." -- Provided by publisher.